Pieter Dirksen, Heinrich Scheidemann’s Keyboard Music: Transmission, Style and Chronology (2007) - Collins, Paul (Journal of the Society for Musicology in Ireland, 2008)
A review of Pieter Dirksen, Heinrich Scheidemann’s Keyboard Music: Transmission, Style and Chronology (Aldershot: Ashgate, 2007), ISBN 978-0-7546-5441-4, xxiii + 254 pp, £55/99.95